2021
DOI: 10.1149/10405.0021ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) How to Achieve Low Thermal Resistance and High Electrothermal Ruggedness in Ga2O3 Devices?

Abstract: Ultra-wide bandgap gallium oxide (Ga2O3) devices have recently emerged as promising candidates for power and RF electronics. The low thermal conductivity of Ga2O3 has arguably been the most serious concern for these devices. Despite many simulation studies, there still lacks an experimental report on the thermal resistance and electrothermal ruggedness of a large-area, packaged Ga2O3 device. Recently, our team for the first time demonstrated largearea Ga2O3 devices with different packaging configurations and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Electrothermal mixedmode simulations revealed that with the double-side package heat is mainly extracted through the junction side in the transient condition; meanwhile, the peak T j is moved from the Schottky contact into the bulk Ga 2 O 3 during the transient heating process (figures 9(c) and (d)). These results illustrate the significance of the package design and cooling configuration on the transient thermal performance and electrothermal ruggedness of Ga 2 O 3 devices [74].…”
Section: Ga 2 O 3 Devicementioning
confidence: 68%
See 1 more Smart Citation
“…Electrothermal mixedmode simulations revealed that with the double-side package heat is mainly extracted through the junction side in the transient condition; meanwhile, the peak T j is moved from the Schottky contact into the bulk Ga 2 O 3 during the transient heating process (figures 9(c) and (d)). These results illustrate the significance of the package design and cooling configuration on the transient thermal performance and electrothermal ruggedness of Ga 2 O 3 devices [74].…”
Section: Ga 2 O 3 Devicementioning
confidence: 68%
“…the encapsulation material and the metal interconnects) also impede the heat flux and result in larger R th [72]. It has been shown throughout the literature that device thermal performance is improved with optimization of device packaging [21,22,24,73,74].…”
Section: Basics Of Power Device/package Thermal Managementmentioning
confidence: 99%
“…reliability, and scalability of the Ga 2 O 3 power devices [6], and hence their competitiveness in power applications.…”
Section: Introductionmentioning
confidence: 99%